Maximum levels of cross‐contamination for 24 antimicrobial active substances in non‐target feed. Part 7: Amphenicols: florfenicol and thiamphenicol - EFSA Panel on Biological Hazards (BIOHAZ) (Wiley, 2021)
Abstract The specific concentrations of florfenicol and thiamphenicol in non‐target feed for food‐producing animals, below which there would not be an effect on the emergence of, and/or selection for, resistance in bacteria relevant for human and animal health, as well as the specific antimicrobial concentrations in feed which have an effect in terms of growth promotion/increased yield, were assessed by EFSA in collaboration with EMA. Details of the methodology used for this assessment, associated data gaps and uncertainties, are presented in a separate document. To address antimicrobial resistance, the Feed Antimicrobial Resistance Selection Concentration (FARSC) model developed specifically for the assessment was applied. The FARSC for florfenicol was estimated. However, due to the lack of data, the calculation of the FARSC for thiamphenicol was not possible until further experimental data become available. To address growth promotion, data from scientific publications obtained from an extensive literature review were used. Levels in feed that showed to have an effect on growth promotion/increased yield were reported for florfenicol, whilst for thiamphenicol no suitable data for the assessment were available. Uncertainties and data gaps associated to the levels reported were addressed. For florfenicol, it was recommended to perform further studies to supply more diverse and complete data related to the requirements for calculation of the FARSC, whereas for thiamphenicol, the recommendation was to generate the data required to fill the gaps which prevented the FARSC calculation.